Screening of novel HSP-inducing compounds to conserve cardiomyocyte function in experimental atrial fibrillation - van Marion DMS; Hu X; Zhang D; Hoogstra-Berends F; Seerden JPG; Loen L; Heeres A; Steen H; Henning RH; Brundel BJJM (Dove Medical Press, 2019)
Denise MS van Marion,1,* Xu Hu,1,* Deli Zhang,1 Femke Hoogstra-Berends,2 Jean-Paul G Seerden,3 Lizette Loen,3 Andre Heeres,3,4 Herman Steen,5 Robert H Henning,2 Bianca JJM Brundel1 1Department of Physiology, Amsterdam Cardiovascular Sciences, VU University Medical Center, Amsterdam, The Netherlands; 2Department of Clinical Pharmacy and Pharmacology, University Medical Center Groningen, Groningen, The Netherlands; 3Syncom BV, Groningen, The Netherlands; 4Hanze University of Applied Sciences, Groningen, The Netherlands; 5Chaperone Pharma BV, Groningen, The Netherlands *These authors contributed equally to this work Background: The heat shock protein (HSP) inducer, geranylgeranylacetone (GGA), was previously found to protect against atrial fibrillation (AF) remodeling in experimental model systems. Clinical application of GGA in AF is limited, due to low systemic concentrations owing to the hydrophobic character of GGA.Objectives: To identify novel HSP-inducing compounds, with improved physicochemical properties, that prevent contractile dysfunction in experimental model systems for AF.Methods: Eighty-one GGA-derivatives were synthesized and explored for their HSP-inducing properties by assessment of HSP expression in HL-1 cardiomyocytes pretreated with or without a mild heat shock (HS), followed by incubation with 10 µM GGA or GGA-derivative. Subsequently, the most potent HSP-inducers were tested for preservation of calcium transient (CaT) amplitudes or heart wall contraction in pretreated tachypaced HL-1 cardiomyocytes (with or without HSPB1 siRNA) and Drosophilas, respectively. Finally, CaT recovery in tachypaced HL-1 cardiomyocytes posttreated with GGA or protective GGA-derivatives was determined.Results: Thirty GGA-derivatives significantly induced HSPA1A expression after HS, and seven showed exceeding HSPA1A expression compared to GGA. GGA and nine GGA-derivatives protected significantly from tachypacing (TP)-induced CaT loss, which was abrogated by HSPB1 suppression. GGA and four potent GGA-derivatives protected against heart wall dysfunction after TP compared to non-paced control Drosophilas. Of these compounds, GGA and three GGA-derivatives induced a significant restoration from CaT loss after TP of HL-1 cardiomyocytes.Conclusion: We identified novel GGA-derivatives with improved physicochemical properties compared to GGA. GGA-derivatives, particularly GGA*-59, boost HSP expression resulting in prevention and restoration from TP-induced remodeling, substantiating their role as novel therapeutics in clinical AF. Keywords: atrial fibrillation, heat shock protein, Drosophila, proteostasis, geranylgeranylacetone